Case study on the singing languages and music learning of six years old foochow children in Sarikei - Wong, Annie Kai Sze (Universiti Putra Malaysia Press, 2010)
The choice of language used in singing has an effect on children’s response towards music. As multiple languages are used among the Foochow community in Sarikei, which is located in Sarawak, East Malaysia, they provide the researcher an opportunity to observe the influence of different languages, namely Mandarin, Malay, English, and Foochow dialect in the song learning process of 16 six year-old children. It was found that children are more musical singing in the Mandarin and Foochow dialect as compared to singing in the languages of Malay and English. The process of urbanization has also caused the vanishing of traditional arts as well as the decline in the usage of Foochow dialects, in which the change of community and environment have affected the enculturation process of language among Foochow children.